Impact of the BIM methodology in the management of construction projects - Gómez-Valdés, Mathias (2023)
In this research, the impact of the BIM methodology in the management of construction projects will be analyzed, recognizing the factors that limit the implementation of this methodology in the construction sector, through the study of existing projects and based on the experience of professionals in the synthesized area in various indexed publications from which a bibliometric analysis was materialized using the Vos Viewer software. BIM, or Building Information Modeling, is a methodology that helps to manage any construction project without discriminating in its size, executing management and coordination of the execution of the entire project from its early phases to the demobilization of the product. The classic CAD methodology has been used for more than two decades and continues to work for numerous construction sites around the world, it is simple to use and implemented by a large number of engineers and architects, but it does not have the same impact as the BIM methodology. which collects much more information than that provided by the traditional methodology. In the projects studied in this research it is possible to recognize multiple advantages and benefits of this methodology that is being implemented little by little in the world, improving the quality of the final project, saving time and costs by reducing extraordinary works or works redone with its application to detect interferences between specialties, improving collaborative work and visualization for the client.